Application of lncRNA–miRNA–mRNA ceRNA network analysis in the treatment of androgenic alopecia. Issue 1 (1st December 2022) - Wei, Hanxiao; Yi, Tian; Li, Qiang; Guo, Yanping; Shen, Caiqi; Jin, Peisheng
Abstract: Background: Long noncoding RNAs (lncRNAs) can be used as competitive endogenous RNAs (ceRNAs) to bind to microRNAs (miRNAs) to regulate gene expression. Previous studies have demonstrated that ceRNAs play an important role in the development of tumors. However, it is not clear whether the lncRNA–miRNA–mRNA ceRNA network plays a role in androgenic alopecia (AGA). Methods: The hair follicles of three AGA patients and three healthy individuals were collected for high‐throughput whole transcriptome sequencing to screen for differentially expressed lncRNAs. Differentially expressed lncRNA target genes were subjected to databases to predict miRNA–mRNA and lncRNA–miRNA relationship pairs, and a ceRNA network was constructed using Cytoscape software. Relative expression was verified by real‐time quantitative reverse transcription–polymerase chain reaction (qRT‐PCR). Results: 84 lncRNAs were significantly differentially expressed between the hair follicles of AGA patients and those of healthy individuals; 30 were upregulated, and 54 were downregulated. The top 10 upregulated lncRNAs were ENST00000501520, ENST00000448179, ENST00000318291, ENST00000568280, ENST00000561121, ENST00000376609, ENST00000602414, ENST00000573866, ENST00000513358, and ENST00000564194. The top 10 downregulated lncRNAs were ENST00000566804, ENST00000561973, ENST00000587680, ENST00000569927, ENST00000340444, ENST00000424345, ENST00000589787, NR_024344, NR_073026, and NR_110001. The qRT‐PCR validation results and receiver‐operating characteristic curve analysis indicated that one upregulated lncRNA, LOXL1‐AS1 (ENST00000564194), had the most significant clinical diagnostic potential. After further analysis, it was concluded that LOXL1‐AS1 could be used as a sponge to target hsa‐miR‐5193, thereby regulating TP53 expression. Conclusion: The ceRNA network‐regulating AGA was constructed through high‐throughput sequencing. Our study also identified a key lncRNA that is possibly related to the AGA pathological process. Abstract : A lncRNA–miRNA–mRNA regulatory network was constructed for the treatment of androgenetic alopecia. We believe that LOXL1‐AS1 (ENST00000564194) has the most significant diagnostic and therapeutic significance. Based on an analysis of the ceRNA regulatory network (A) and database (B‐C), LOXL1‐AS1 may sponge hsa‐miR‐5193 by acting as a ceRNA, thereby participating in the regulation of TP53 expression. Studying the expression profile of AGA lncRNAs and identifying new biomarkers are of great significance for providing potential targets and new therapeutic ideas for AGA diagnosis and treatment.